Effect of ZnO nanoparticle on cell viability, zinc uptake efficiency, and zinc transporters gene expression: a comparison with ZnO and ZnSO4 - Xiangfei Zhang; Zhisheng Wang; Lei Mao; Xianwen Dong; Quanhui Peng; Juncai Chen; Cui Tan; Rui Hu (Czech Journal of Animal Science, 2017)
Zinc plays an important role in functional and structural integrity of cells. The aim of the current study was to compare cell viability, zinc uptake efficiency, and gene expression of metallothionein (MT), divalent metal transporter (DMT-1), and other important zinc transporters (ZnTs) under experimental treatment of TPEN (N, N, N', N'-Tetrakis (2-pyridylmethyl) ethylenediamine) (2 µM), and three zinc sources (zinc oxide nanoparticle (nano-ZnO), bulk zinc oxide (ZnO), and zinc sulfate (ZnSO4)) at different levels (25, 50, and 100 µM) in rat intestinal epithelial cell line IEC-6. Cells were classified into TPEN group and TPEN + zinc sources groups. In the present study, significantly decreased cell viability was observed in TPEN group, while supplementations with nano-ZnO at all levels and ZnO (50 and 100 µM) significantly increased the cell viability. ZnSO4 at a high concentration (100 µM) inhibited cell viability. Furthermore, cells of nano-ZnO group showed the highest viability at a 25 µM concentration. The uptake efficiency of nano-ZnO is higher than that of ZnSO4 and ZnO. Additionally, a significant down-regulation for ZnT-1, ZnT-4, MT, DMT-1 mRNA with TPEN treatment was detected. Compared with the unchanged ZnT-4, all zinc treatments up-regulated the gene expressions of ZnT-1, ZnT-5, ZnT-7, MT, and DMT-1. Our results indicate that nano-ZnO is more effective than ZnO and ZnSO4 in enhancing cell viability, and its lower cytotoxicity, higher uptake efficiency, and comparative transportation at low concentration also favour its potential use as a new zinc source in feed additives.